Modelo matemático no lineal en un sistema de temperatura para un recinto cerrado (2013)
In this article the mathematical model is explained for a didactic control module where the temperature variable is analyzed. The model being used is necessary to simulate the dynamics of the process and develop some control strategies that can be applied in a real system. With this purpose in mind, it is important that the model, which is not the only one, is a trustworthy representation of the purpose of analysis. To obtain the mathematical model, the gray box system is carried out. Here, the mathematical equations that rule the behavior of the process are known in terms of dynamic parameters of the system applied; this is why that the obtaining of the mathematical model is divided into two parts. The first one has to do with the physical equations of the system in terms of some unknown parameters. The second one deals with the way these parameters are found by using minimum squares. Once the mathematical model was done, its worthiness was confirmed. For such a purpose, the validity of the model was proved and it was found to be adequate. This system identification technique can be applied in other process with known physical equations in terms of unknown parameters.